ปัจจัยเสี่ยงของภาวะตับอักเสบเรื้อรังในผู้ป่วยไทยที่ติดเชื้อเอชไอวี ที่ไม่พบเชื้อไวรัสตับอักเสบชนิดบีหรือซีร่วมด้วย - เทพ เฉลิมชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The objectives of this study were to determine clinical demographics and risk factors of chronic hepatitis in antiretroviral (ARV)-treated HIV infection, without hepatitis B or C viral infection. Nested case-control study of HIV infected, matched by the starting date of anti-retroviral treatment, during Nov 2002-July 2012 was conducted. The cases were defined as those with elevated ALT > 40 IU/L at 2 consecutive visits 6 months apart and the controls were defined as those with never had 2 consecutive ALT > 40 IU/L and normal ALT < 40 IU/L at last visit. Both groups had normal ALT at pre-ARV initiation. Clinical demographics and risk factors of chronic hepatitis including HIV-related illness, anti-retroviral treatment and metabolic diseases were collected and analyzed. Conditional logistic regression was used to determine risk factors of chronic hepatitis in HIV infection. A total of 124 matched pairs with HIV infection were followed over 3,195 person-years. The incidence rate of chronic hepatitis was 5.4 per 100 person-years. The mean age (+SD) was 33.0 + 7.3 years with 41.1% in male. The mean (+SD) time from an initiation of ARV to chronic hepatitis was 2.3 + 2 years. Male gender (adjusted Odds ratio, OR, 95% CI: 3.1, 1.5-6.6, p = 0.002) and high body mass index (BMI > 23 kg/m2, adjusted OR, 95% CI: 2.3, 1.1-4.6, p = 0.02) were the independent risk factors of chronic hepatitis by multivariate analysis. In conclusion, male gender and high body mass index were the main risk factors of chronic hepatitis in HIV infected individuals without hepatitis B or C infection.